Patterns and predictors of air purifier adherence in children with asthma living in low-income, urban households. (4th May 2022) - Kaviany, Parisa; Brigham, Emily P.; Collaco, Joseph M.; Rice, Jessica L.; Woo, Han; Wood, Megan; Koehl, Rachelle; Wu, Tianshi D.; Eakin, Michelle N.; Koehler, Kirsten; Hansel, Nadia N.; McCormack, Meredith C.
Abstract: Objective: Black children and children from low-income communities are disproportionately affected by asthma, attributed partly to pollution exposure. Air purifiers reduce indoor air pollution and improve asthma symptoms in children. In order to implement air purifier interventions, an understanding of patterns of use and potential barriers is necessary. Methods: In a home intervention study, 127 children with asthma living in Baltimore were randomized to receive two active or two placebo air purifiers. The 16-week study period included: baseline clinic visit, home visit for air purifier installation (active or placebo) with instruction to use the high or turbo settings, and electronic adherence monitoring of air purifiers. Determinants of adherence were identified using linear regression models. Results: Air purifiers were used 80% of the time, and participants demonstrated adherence to high or turbo settings for 60% of the time. In an adjusted model, season was the major determinant of air purifier adherence, with 21% lower use in the winter ( p = 0.025) attributed to the cold draft generated by the machine. Conclusion: In a clinical trial with electronic adherence monitoring, air purifier use was high and participants were adherent to use of high or turbo settings the majority of the time. Addressing practical barriers to consistent use, such as draft during the winter, in addition to financial barriers may improve air purifier adherence among children with asthma living in low-income, urban households. Clinical Trials Registry Number: NCT02763917.